Postgraduate training in gynecology and obstetrics. Results of an individual national survey of interns. - Lourenço, A V; Nunes, F; Martins, A T; Saraiva, J (Acta Médica Portuguesa, 1996)
The national survey on the trainees in this specialty was conducted to find out the trainees' opinions and expectations regarding postgraduated in Gynecology and Obstetrics and professional opportunities. A total of 320 questionnaires were send to all the trainees registered with the Portuguese Medical Association. Some of the topics of this survey were: structure and quality; curriculum requirements; assessment and professional opportunities. We received a total of 109 replies, which are presented in this article.